Social Media – Educational and Pedagogical Problems - Zeler, Bogdan (European Journal of Multidisciplinary Studies, 2018)
Communicational behaviour has undergone more and more dynamic transformations together with the appearance of the further forms of these media such as blogs and video blogs, social networks, communications applications especially Facebook and Twitter. The initial enthusiasm has gradually faded to a large extent and has been even replaced with elements of criticism. Web 2.0 media have the element of risk which can be generally understood as probability of occurrence of something unpredictable. Our anxiety connected with the media often has intuitional character, or it is a futurological self-fulfilling prophecy. We are often surprised with the way the media are used, it also refers to the consequences of entering the world of Web 2.0 media. These elements of risk are connected with such issues as identity, anonymity, identity theft, hate speech, Internet hate and trolling. Recently fake news have become a particular danger. Numerous communicational activities involve bots. Social media instead of connecting create informational filter bubbles. These communicational changes raise a question concerning the form of education and pedagogy, and about the character of activities on this field in which young people in the period of Web 2.0 media should participate. What new competences (social, personal, cultural, technical) are required in this new form of communication. Contemporary theories and currents in education are not always useful, even such radical ones as post-pedagogy and postmodern pedagogy. It seems to be crucial to indicate rules which will allow young users of ‘new new media’ to find their way in axiological space where constant values which so far have been the bastion of educational process are exposed to adiaforisation – the process of liberating some categories of actions from moral judgment, finding them ethically indifferent. ‘Coming of Age in Second Life’, the appearance of new anthropology of virtual man, to quote the book by Tom Boellstorff, makes us reconsider those educational and pedagogical contexts.